Impact of Modern Marketing Strategies Over Hotel Industry - Naiya Rana; Nilesh Ratnoday (AG Volumes, 2021)
To get more reservations and make more money, you'll need hotel marketing on your side. Customers will learn about the hotel along with its values as well “unique selling proposition” mostly via your marketing communications. Of course, keeping up with current trends is essential if you want to maximise your marketing efforts. The emergence of covid, on the other hand, has altered hotel marketing patterns. New marketing strategies were present from pre-covid era but its integration and implementation after covid impact became an essential approach. This research aimed to understand the modern marketing strategies over hotel industry and its business, especially after covid. A survey has been conducted with the help of which 104 responses were gathered. It is concluded that covid-19 significantly impacted the business strategies and also, new marketing strategies have significantly impacted.